Cold War, Press Freedom and Journalism Education: Paradoxes of the Untypical 1968 IAMCR Conference in Pamplona - Barrera, Carlos (Javnost-The Public, 2019)
In the context of the Cold War that affected the first steps of the International Association for Media and Communication Research (IAMCR), journalism education was the topic dealt by attendees from West and East Europe during the 1968 conference in Pamplona, Spain. Paradoxically professors from communist countries spoke openly in an event partly sponsored by Spain's anti-communist regime. Indirectly, the lack of press freedom in the late dictatorship caused some incidents due to some Spanish professors’ critical speeches. Beyond these controversies related to domestic issues, depoliticisation—in accordance with the original spirit of IAMCR—became a key strategy for the conference success as a whole. The election of Pamplona, located in a non-aligned country, as the conference's venue meant a break in the struggle to gain power and influence within the organisation. This story, based on unpublished documents from the University of Navarra's School of Communication, sheds light on several intertwined issues such as international academic cooperation beyond the post World War II East–West confrontation, and press liberalisation in authoritarian regimes through journalism education. It is also a contribution for a more accurate knowledge of the life of IAMCR as a worldwide organisation in the field of communication research.